Propuesta de manejo de neumáticos usados en la ciudad de Quevedo - Meza Lay, Ana Gabriela (2015)
The research study entitled "Proposal for management of used tires in the city of Quevedo", was conducted in the urban area of the canton Quevedo, province of the rivers, whose general objective is to propose an alternative in the environmental management of used tires generated by the fleet of Quevedo; specific goals were the following: A diagnostic of the current situation of handling of used tires in the city Quevedo, which was performed by using surveys to employees in establishments; Estimating rates of generation of tires used by type of generator and tire, was carried out by means of a control of 12 consecutive weeks in the collection centers; determine the feasibility of implementation of alternative treatment and final disposal of used tires, where it was considered bibliographic references in the management in other countries of the economically viable alternatives. It was determined that in the urban area of the canton Quevedo there are 35 centers among which 28 vulcanizadoras were found, 4 tecnicentros, 2 shops and 1 commercial. The viable alternatives are: containment wall, children's games, making furniture and pots. In accordance with the results obtained, it accepts the alternative hypothesis "There is the possibility of applying an environmental alternative to use the tires used in the city of Quevedo". It is concluded that the establishments that more waste generated are the vulcanizadoras, those from the smaller shops and commercial. The quantity of tires generated weekly is constant with an average of 481 used tires. It is recommended that the GAD municipal de Quevedo implements specific regulations for the proper management of used tires.